Profile of children with increased intracranial pressure on mannitol treatment - Sander D Teddy; Abdul Latief; Bambang Madiyono (Indonesian Pediatric Society Publishing House, 2016)
Background Early recognition of increased intracranial pressure (IIP) and well-monitored management are determining indicators for treatment outcome. As far as we know, data of children with IIP on mannitol treatment has not been available. Objective To elicit the profile of IIP patients who received mannitol at the Department of Child Health, Cipto Mangunkusumo Hospital, Jakarta. Methods This was a cross-sectional study. Data were obtained from medical records of patients with increased intracranial pres- sure who received mannitol at the Department of Child Health, Cipto Mangunkusumo Hospital, Jakarta between July 2001 to Oc- tober 2003 Results Fifty-four IIP patients with mannitol treatment were included. Forty-two (78%) were under-five years old. Thirty-six subjects (67%) were boys; 30 (56%) were undernourished. Central nervous system infections (meningitis and encephalitis) were the most frequent causes of IIP. Most of the head CT scan revealed cerebral edema, hydroceph- alus, and cerebral hemorrhage. Fifty subjects (93%) had decline of con- sciousness; most of them were somnolent. Improvement in conscious- ness was identified in 31 subjects, in which 21 subjects reached full consciousness. Vomiting, which was found in 25 subjects (46%), sub- sided after mannitol administration. Behavioral changes were found in 49 subjects (91%); 32 subjects still had persistent behavioral changes after mannitol administration. Large and protruding fontanel was found in 7/22 subjects, cerebral nerve paralysis in 23 subjects (43%) and papillary edema in 6 of 34 subjects who underwent funduscopy. During the treatment with mannitol, fever was found in 5 subjects, vomiting in 2 subjects, skin edema and tachycardia each in 1 subject. Metabolic aci- dosis was found in 6/13 subjects, hyponatremia and hypokalemia in 16 and 13 out of 30 subjects respectively. Death occurred in 9 subjects (17%). Conclusion In IIP patients, the administration of mannitol has a tendency to improve consciousness, vomiting, and behavioral or personality changes. The high incidence rate of electrolyte imbal- ances and metabolic acidosis during the treatment indicated the need of periodic monitoring to detect early disorders.